Odorant metabolism of the olfactory cleft mucus in idiopathic olfactory impairment patients and healthy volunteers. Issue 3 (12th October 2021) - Ijichi, Chiori; Wakabayashi, Hidehiko; Sugiyama, Shingo; Hayashi, Kazuhiro; Ihara, Yusuke; Nishijima, Hironobu; Touhara, Kazushige; Kondo, Kenji
Abstract: Background: It remains unclear whether the metabolic activity of nasal mucus in the olfactory and respiratory areas is different. Moreover, age‐ and olfaction‐related changes may affect metabolism. Methods: Hexanal, octanal, and 2‐methylbutanal were selected for in vitro metabolism analysis and compared between the olfactory cleft and respiratory mucus of participants < 50‐year‐old with normal olfaction using gas chromatography mass spectrometry. The metabolic activity of hexanal in the olfactory cleft mucus was further compared between three groups, (1) normal olfaction, age < 50 years old, (2) normal olfaction, age ≥50 years old, and (3) idiopathic olfactory impairment. To characterize the enzyme(s) responsible for aldehyde reduction, we also tested if epalr22897estat and 3, 5‐dichlorosalicylic acid, types of reductase inhibitors, affect metabolism. Results: Conversion of aldehydes to their corresponding alcohols was observed in the olfactory cleft and respiratory mucus. The metabolic production of hexanol, octanol, and 2‐methybutanol was significantly higher in the olfactory cleft mucus than in the respiratory mucus ( p < 0.01). The metabolic conversion of hexanal to hexanol in the mucus of the idiopathic olfactory impairment group was significantly lower than that in the age‐matched normal olfaction group. Excluding the nicotinamide adenine dinucleotide phosphate (NADPH) regenerating system from the reaction mixture inhibited metabolism. The addition of either epalr22897estat or 3, 5‐dichlorosalicylic acid did not inhibit this metabolic conversion. Conclusions: The enzymatic metabolism of odorants in the olfactory cleft mucus is markedly higher than in the respiratory mucus and decreases in patients with idiopathic olfactory impairment.